Disparities in sinonasal squamous cell carcinoma short‐ and long‐term outcomes: Analysis from the national cancer database. (16th August 2017) - Carey, Ryan M.; Parasher, Arjun K.; Workman, Alan D.; Yan, Carol H.; Glicksman, Jordan T.; Chen, Jinbo; Palmer, James N.; Adappa, Nithin D.; Newman, Jason G.; Brant, Jason A
Abstract : Objectives/Hypothesis: To examine sociodemographic, hospital‐specific, and disease‐related characteristics in relation to outcomes in sinonasal squamous cell carcinoma (SCC). Study Design: The National Cancer Database was queried for location codes corresponding to the nasal cavity and paranasal sinuses and histology codes representing SCC malignancy. Multivariate analyses were performed against short‐ and long‐term outcomes (overall survival, days to discharge, 30‐day readmission, and 30‐ and 90‐day mortality). Results: The database included 5, 584 sinonasal SCC patients with an overall median survival of 53.5 months (95% confidence interval [CI]: 49.7‐57.8). On multivariate analysis, uninsured, Medicaid, and Medicare were independently associated with worse overall survival compared to private insurance (hazard ratio [HR]: 1.49, 95% CI: 1.22‐1.82, P < .001; HR: 1.57, 95% CI: 1.34‐1.85, P < .001; and HR: 1.14, 95% CI: 1.01‐1.29, P = .03, respectively). Both Medicaid and Medicare were also associated with increased 30‐day mortality (HR: 1.36, 95% CI: 1.76‐143.29, P = .02; HR: 8.27, 95% CI: 1.66‐70.88, P = .02, respectively), and Medicaid patients spent more time in the hospital following surgery (difference in days to discharge: HR: 2.09, 95% CI: 0.57‐3.61, P < .01). Compared to white race, other race was associated with improved overall survival (HR: 0.79, 95% CI: 0.63‐0.99, P = .04) but increased 30‐day readmissions (HR: 3.85, 95% CI: 1.58‐8.38, P < .01). Hispanic ethnicity was associated with increased 30‐day readmissions (HR: 2.35, 95% CI: 1.08‐4.75, P = .02]. The highest income bracket (≥$63, 000) was associated with fewer hospital readmissions (HR: 0.33, 95% CI: 0.13‐0.79, P = .01). Conclusions: Sociodemographic and economic differences in outcomes of patients with sinonasal SCC cancer exist. An understanding of these differences may help minimize disparities in oncologic treatment. Level of Evidence: 2c. Laryngoscope, 128:560–567, 2018